Magnetic Interplay between π‐Electrons of Open‐Shell Porphyrins and d‐Electrons of Their Central Transition Metal Ions. Issue 19 (18th March 2022) - Sun, Qiang; Mateo, Luis M.; Robles, Roberto; Ruffieux, Pascal; Bottari, Giovanni; Torres, Tomás; Fasel, Roman; Lorente, Nicolás
Abstract: Magnetism is typically associated with d ‐ or f ‐block elements, but can also appear in organic molecules with unpaired π ‐electrons. This has considerably boosted the interest in such organic materials with large potential for spintronics and quantum applications. While several materials showing either d / f or π ‐electron magnetism have been synthesized, the combination of both features within the same structure has only scarcely been reported. Open‐shell porphyrins (Pors) incorporating d ‐block transition metal ions represent an ideal platform for the realization of such architectures. Herein, the preparation of a series of open‐shell, π ‐extended Pors that contain magnetically active metal ions (i.e., Cu II, Co II, and Fe II ) through a combination of in‐solution and on‐surface synthesis is reported. A detailed study of the magnetic interplay between π ‐ and d ‐electrons in these metalloPors has been performed by scanning probe methods and density functional theory calculations. For the Cu and FePors, ferromagnetically coupled π ‐electrons are determined to be delocalized over the Por edges. For the CoPor, the authors find a Kondo resonance resulting from the singly occupied Co II d z 2 orbital to dominate the magnetic fingerprint. The Fe derivative exhibits the highest magnetization of 3.67 μB (S≈2) and an exchange coupling of 16 meV between the π ‐electrons and the Fe d ‐states. Abstract : Using a combination of in‐solution and on‐surface chemistry, three π ‐extended metallo‐porphyrins are prepared (namely, CuPorA2, CoPorA2, and FePorA2 ). An atomic‐scale study of these nanostructures—by scanning probe microscopy and density functional theory—reveals a magnetic interplay between the π ‐ and d ‐electrons. The presented approach paves the way towards the realization of fascinating novel materials with intriguing magnetic properties.